2018
DOI: 10.1161/jaha.117.008268
|View full text |Cite
|
Sign up to set email alerts
|

Combined Angiotensin Receptor–Neprilysin Inhibitors Improve Cardiac and Vascular Function Via Increased NO Bioavailability in Heart Failure

Abstract: BackgroundThere is a paucity of data about the mechanisms by which sacubitril/valsartan (also known as LCZ696) improves outcomes in patients with heart failure. Specifically, the effects of sacubitril/valsartan on vascular function and NO bioavailability have not been investigated. We hypothesized that sacubitril/valsartan therapy increases circulating NO levels and improves vascular function in the setting of heart failure.Methods and ResultsMale spontaneously hypertensive rats underwent myocardial ischemia/r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…In this study, we demonstrated that both enalapril and LCZ696 improved LVEF and that LCZ696 therapy led to a greater effect on LVEF. As compared with enalapril therapy, the additional effects of LCZ696 may be attributed to inhibition of cardiac fibrosis [15], suppression of proinflammatory cytokine [16], and enhancement of nitric oxide (NO) bioavailability [17]. In a report by von Lueder et al, LCZ696 therapy reduced degree of fibrosis in noninfarct remote myocardium in the peri-infarct zone [15].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that both enalapril and LCZ696 improved LVEF and that LCZ696 therapy led to a greater effect on LVEF. As compared with enalapril therapy, the additional effects of LCZ696 may be attributed to inhibition of cardiac fibrosis [15], suppression of proinflammatory cytokine [16], and enhancement of nitric oxide (NO) bioavailability [17]. In a report by von Lueder et al, LCZ696 therapy reduced degree of fibrosis in noninfarct remote myocardium in the peri-infarct zone [15].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular function was measured in isolated segments (3 mm in length) of thoracic aorta as previously described (27) at 18 weeks following TAC in all study groups. Vascular rings were equilibrated for 60 min and then pre-contracted with phenylephrine (1 μM).…”
Section: Methodsmentioning
confidence: 99%
“…Relatively little is known about the effects of SAC/VAL on diastolic function, and in particular, about the effects on diastolic function in MHD or models of HFpEF. In 1 study, SAC/VAL improved LV relaxation in spontaneously hypertension rats with heart failure induced by myocardial ischemia/reperfusion ( 22 ).…”
Section: Discussionmentioning
confidence: 99%